Implementasi Model Pembelajaran Problem Based Learning (PBL) Berbantuan Lembar Aktivitas Siswa (LAS) Untuk Meningkatkan Kemampuan Siswa Dalam Memecahkan Masalah Matematika - Evi Kholisoh; Achmad Buchori; Amanati Rochmah; Lilik Ariyanto (Departement of Mathematics Education, 2024)
This article discusses the implementation and results of implementing the Problem-Based Learning Model (PBL) using Student Activity Sheets (LAS) to evaluate the development of mathematical problem-solving abilities of class X MPLB 1 students at SMK N 2 Semarang on the topic of single interest and compound interest. Class X MPLB 1, consisting of 36 students, is the focus of this research. The research method was carried out in two cycles, where each cycle consisted of two meetings. The data collected comes from observations and tests, which are then analyzed using descriptive techniques. The research results showed that there was a significant increase in problem-solving abilities from cycle I to cycle II. Initially, the average problem-solving ability was 67.78, which then increased to 75 in cycle I and continued to increase to 88 in cycle II.